Nucleotide-Specific Contrast for DNA Sequencing by Electron Spectroscopy - Mankos, Marian (PLoS One, 2016)
DNA sequencing by imaging in an electron microscope is an approach that holds promise to deliver long reads with low error rates and without the need for amplification. Earlier work using transmission electron microscopes, which use high electron energies on the order of 100 keV, has shown that low contrast and radiation damage necessitates the use of heavy atom labeling of individual nucleotides, which increases the read error rates. Other prior work using scattering electrons with much lower energy has shown to suppress beam damage on DNA. Here we explore possibilities to increase contrast by employing two methods, X-ray photoelectron and Auger electron spectroscopy. Using bulk DNA samples with monomers of each base, both methods are shown to provide contrast mechanisms that can distinguish individual nucleotides without labels. Both spectroscopic techniques can be readily implemented in a low energy electron microscope, which may enable label-free DNA sequencing by direct imaging.